Introduction to Business - Gitman, Lawrence J.; McDaniel, Carl; Shah, Amit; Reece, Monique; Koffel, Linda; Talsma, Bethann; Hyatt, James C.; Open Textbook Library (Open Textbook Library, 2018)
Introduction to Business covers the scope and sequence of most introductory business courses. The book provides detailed explanations in the context of core themes such as customer satisfaction, ethics, entrepreneurship, global business, and managing change. Introduction to Business includes hundreds of current business examples from a range of industries and geographic locations, which feature a variety of individuals. The outcome is a balanced approach to the theory and application of business concepts, with attention to the knowledge and skills necessary for student success in this course and beyond.
Chapter 1: Understanding Economic Systems and Business -- Chapter 2: Making Ethical Decisions and Managing a Socially Responsible Business -- Chapter 3: Competing in the Global Marketplace -- Chapter 4: Forms of Business Ownership -- Chapter 5: Entrepreneurship: Starting and Managing Your Own Business -- Chapter 6: Management and Leadership in Today's Organizations -- Chapter 7: Designing Organizational Structures -- Chapter 8: Managing Human Resources and Labor Relations -- Chapter 9: Motivating Employees -- Chapter 10: Achieving World-Class Operations Management -- Chapter 11: Creating Products and Pricing Strategies to Meet Customers' Needs -- Chapter 12: Distributing and Promoting Products and Services -- Chapter 13: Using Technology to Manage Information -- Chapter 14: Using Financial Information and Accounting -- Chapter 15: Understanding Money and Financial Institutions -- Chapter 16: Understanding Financial Management and Securities Markets -- Chapter 17: Your Career in Business
In English.
Description based on online resource
Keywords: Management -- Textbooks